Aumento da vida útil de lombo suíno temperado (a seco e marinado) pelo uso de conservantes naturais - Souza, Ianamara Santorum de (2023)
The widespread use of synthetic chemical additives by the food industry has been associated with health risks for consumers. In this context, the meat industry has been looking for natural alternatives to extend the useful life of products. The present study aimed to evaluate the feasibility of applying natural preservative and stabilizing ingredients to chilled pork meat products seasoned by dry and wet methods, in order to extend shelf life and maintain physical-chemical and sensorial quality characteristics similar to conventional products. Eight formulations (F) of lean pork cuts (loin) were prepared, 4 of which were prepared by dry curing (F1s, F2s, C1s, C2s) and 4 by wet curing with 15% brine injection (F1u, F2u, C1u, C2u ), using, in addition to seasonings and salt, natural preservatives, namely: F1s and F1u, with 1.5% organic acids, their salts and peptides and; F2s with 1.5% organic acids, its salts and peptides, 0.30% acerola extract, and 0.20% beetroot extract, F2u, in addition to those mentioned for F2s 0.7% yeast extract and citrus, compared to controls (C1s, C1u) with synthetic preservatives, and (C2s and C2u) without preservatives. The formulations were evaluated for proximate composition, pH, instrumental color L*, a*, b*, C* and h°, water activity (Aw), and oxidative stability by determining the percentage of metmyoglobin and TBARS index at times 0, 15, 30 and 45 days at 7 °C, and also regarding microbiological stability for 45 days at 2 and 7 °C. After elaboration, the samples were also evaluated for weight loss after cooking at 180 °C for 1 hour and sensory acceptance using a hedonic scale and purchase intention by 120 untrained evaluators. The data obtained were evaluated by ANOVA and Tukey test (p < 0.05). The formulations met the legislation regarding proximate composition, with protein content above 20%, with no difference between samples (p > 0.05). The moisture content of wet-cured samples (73-74%) was higher than that of dry-cured samples (70-72%) (p < 0.05). Lipid contents were below 0.82% and minerals between 2.1 and 3.2%. Considering the pH (5.6 to 5.8) and Aw (0.97 to 0.98) parameters, natural ingredients would provide stability close to synthetic additives. Formulations F2s and F2u stood out with higher C* and hº values similar to control samples and with storage stability. All samples presented a TBARS index < 1 mg of malonaldehyde kg-1 for 45 days, within the recommended range. Lower metmyoglobin formation rates were observed in the F1s and F1u formulations. It was not possible to verify a positive effect of the natural ingredients against microorganisms after 15 days at 7 °C. When the product was stored at 2 °C, it remained stable for up to 30 days (wet curing) and up to 45 days (dry curing) and stored. The mixture of yeast extract and citrus extract provided greater yield with lower cooking loss (p < 0.05). Sensorially, natural ingredients proved to be promising alternatives, in addition to the positive effects on product conservation and increased shelf life, they maintained high acceptance in all sensorial aspects evaluated, potentially making natural seasoned pork products more competitive on the market.